A study on information focus at sentence level in English Economics News = Nghiên cứu về tiêu điểm thông tin ở cấp độ câu trong các tin kinh tế tiếng Anh. M.A. Thesis Linguistics: 60 22 15 - Vũ, Thị Thanh Thúy (University of Foreign Languages and International studies, 2017)
M.A. Thesis English Linguistic -- University of Foreign Languages and International studies. Vietnam National University, Hanoi, 2011